Optical temperature measurements in superheated liquid droplets; Experimental Thermal and Fluid Science; Vol. 175 - Nichik M. Yu. Mikhail Yurjevich; Cherkasov R. E. Roman Evgenjevich; Antonov D. V. Dmitry Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Zotjeva A. A. Anastasiya Aleksandrovna; Dulin V. M. Vladimir Mikhaylovich; Castanet G. Guillaume; Sazhin S. S. Sergey Stepanovich (2026, 2026)
Title screen